2017
DOI: 10.1039/c7fo00486a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of zeaxanthin on 3T3-L1 preadipocyte and high fat induced obese mice

Abstract: Zeaxanthin, a type of carotenoid, has been proven to exhibit anti-lipogenesis effect; however, the detailed mechanism of this effect is less known. Herein, we evaluated the effects of zeaxanthin on the inhibition of adipogenesis in 3T3-L1 adipocytes and obesity in high-fat diet fed C57BL/6J mice. Zeaxanthin significantly decreased the intracellular lipid content in a dose-dependent manner (5-15 μM) in adipocytes without causing cytotoxicity. In high-fat-diet-induced obese mice, oral administration of 20 mg kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…To measure the effect of Rg1 on gene expression in white adipose tissue and 3T3-L1 cells, RT-PCR were performed as previously described [ 24 ]. Briefly, total RNA was isolated using RNA iso Plus reagent (TaKaRa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…To measure the effect of Rg1 on gene expression in white adipose tissue and 3T3-L1 cells, RT-PCR were performed as previously described [ 24 ]. Briefly, total RNA was isolated using RNA iso Plus reagent (TaKaRa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Various compounds with lipolytic activity and anti-lipogenesis activity were isolated as potential drug candidates from herbal medicines and natural products used to prevent accumulation of body fat. To date, many studies report anti-obesity effects after the treatment of several natural compounds such as resveratrol [ 19 ], ramalin [ 20 ], zeaxanthin [ 21 ], and eupatilin [ 22 ]. In this study, we tried to obtain scientific evidences of the role of morusin on the inhibition of lipogenesis and stimulation of lipolysis in 3T3-L1 cells and primary adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, previous studies have used them as distinct markers to identify novel compounds with anti-obesity activity. Although the expression levels of adipogenic transcription factors and lipogenic proteins are significantly increased in MDI-stimulated 3T3-L1 cells, these levels recovered after treatment with several single compounds isolated from natural products including resveratrol [ 19 ], ramalin [ 20 ], zeaxanthin [ 21 ], and eupatilin [ 22 ]. Results of this current study are consistent with previous studies; we observed a decrease of two adipogenic transcription factors and two lipogenic proteins in MDI-stimulated 3T3-L1 cells after morusin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations